2018
DOI: 10.1111/lam.13034
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antifungal susceptibility of Candida species among pregnant women attending a school maternity at Natal, Brazil

Abstract: Vulvovaginal candidiasis (VVC) is a problem that affects a significant number of pregnant women worldwide. This type of fungal infection generates great discomfort due to the symptomatology and difficulties of diagnosis and treatment. In view of the scarcity of data in the State of Rio Grande do Norte, Brazil, regarding studies carried out on fungal populations of the genus Candida associated with VVC in pregnant women, this study considered relevant, the phenotypic and genotypic identification of the species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
10
0
3
Order By: Relevance
“…in the majority of the cases. The highest prevalence of C. albicans that had been recorded from the samples of pregnant women was 95% in Natal, Brazil [ 36 ]. Dias et al [ 34 ] also had found a prevalence of 92.3% for C. albicans in Mato Grosso, Brazil.…”
Section: Prevalence Of Vulvovaginal Candidosis During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…in the majority of the cases. The highest prevalence of C. albicans that had been recorded from the samples of pregnant women was 95% in Natal, Brazil [ 36 ]. Dias et al [ 34 ] also had found a prevalence of 92.3% for C. albicans in Mato Grosso, Brazil.…”
Section: Prevalence Of Vulvovaginal Candidosis During Pregnancymentioning
confidence: 99%
“…C. albicans was found to be significantly associated with gestational diabetes [ 33 ]. Nevertheless, several studies did not find any significant statistical relationship between diabetes and VVC during pregnancy [ 29 , 36 , 43 ]. Guzel et al [ 11 ] also found no association of DM with the prevalence of candida vaginitis during pregnancy.…”
Section: Risk Factors Of Vvc During Pregnancymentioning
confidence: 99%
“…Among many causes of vaginitis, VVC is the second most common and is diagnosed in 40% of women with vaginal complaints in the primary care setting [6,28,29] and it is a problem that is known to affect significant number of pregnant women worldwide [30][31][32][33]. Of all Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…All samples were obtained from the posterior fornix of the vagina with sterilized vaginal swabs and initially examined by gram stain, followed by inoculation on malt extract agar (Difco) supplemented with chloramphenicol (50 mg/ml), CHROMagar Candida medium (CHROMagar Company, Paris, France) to ensure purity, and incubated at 35-37 °C for 48 h [ 7 ]. Approval of the research was acquired from the Research Ethics Committee of the Fasa University of Medical Sciences (IR.FUMS.REC.1395.85), and written consent was obtained from all patients involved.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies reported that Candida albicans is predominantly involved in VVC, followed by Candida glabrata , Candida tropicalis , Candida parapsilosis , and Pichia kudriavzevii ( Candida krusei ) [ 4 , 6 , 7 ]. Nevertheless, the increasing prevalence of non- albicans Candida species with a reduced susceptibility acquired resistance or intrinsic resistance to the antifungal drugs currently administered has become the most important issue of treatment failure, over the past decade [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%